Da'wah Through Animation Media in the Perspective of Da'wah Verses - Adam Hafidz Al Fajar; Al Kahfi; Pajar Hatma Indra Jaya (Jurnal Dakwah dan Komunikasi, 2024)
This research aims to explore the potential of animation media as a tool for da'wah from the perspective of Quranic verses relevant to the principles of da'wah. Animation media was chosen due to its high visual appeal, its ability to simplify complex religious concepts, and its relevance to the lifestyle of the digital generation. In this study, a qualitative method with a descriptive-analytical approach was used. Data were collected through a literature review of Islamic sources, content analysis of available Islamic animation, and interviews with experts in the fields of da’wah and animation media. The results indicate that animation has great potential to support da’wah by delivering Islamic values in an engaging manner, especially for children and young generations. Other findings show that the use of animation as a media for da’wah often does not fully leverage the principles of Islamic da’wah as outlined in Quranic verses such as QS. An-Nahl: 125 and QS. Ali Imran: 104. The main challenges identified include the lack of high-quality Islamic animation production, limited understanding of audience preferences, and the dominance of non-Islamic content on digital platforms. This research concludes that a more systematic strategy is needed to integrate Islamic da’wah values into animation production. With the right approach, animation can become an effective and relevant media for supporting the spread of Islamic values in the digital age